The 'Urbanforest' and 'Green space' Classification Model in the Spatial Arrangement of Registro-SP, Brazil - Ajibola Isau Badiru; Ana Cristina Machado Rodríguez; Maria Aparecida Faustino de Pires (European Regional Science Association (ERSA), 2005)
The necessity of handling green areas relating to urban settings has become one of the vital environmental challenges in view of several accumulated environmental problems in the last few decades. In United States and Canada, many investments are being made for new techniques and instruments that are needed in environmental planning involving urban forest researches both in the local and national scale. However, there are few reports on urban forest classification connecting spatial characteristics, physical structures involving pattern and process. With the objective to classify urban green areas for integrated approach, this research have focused on urban pattern for an effective understanding of urban forest concept, green areas and urban vegetation types. The urban morphology in consistency with the urban forest Focus Chat (FC) recently designed has been applied to characterize spatial categories of urban vegetation involved in the urban arrangement of Registro-SP. Method has integrated zones, patterns and processes for technical analyses to contemplate the urban dynamics, occupation and land use. Categories of urban forest and vegetation types were derived for the urban planning and system management. The resulting pattern can be technically monitored in the use of suitable GIS (Geographical Information System) software for physical and environmental records.
Keywords: 330